2017
DOI: 10.1017/s0021932017000487
|View full text |Cite
|
Sign up to set email alerts
|

Birth Order, Stage of Infancy and Infant Mortality in India

Abstract: SummaryUsing data from India's National Family Health Survey, 2005-06 (NFHS-3), this article examines the patterns of relationship between birth order and infant mortality. The analysis controls for a number of variables, including mother's characteristics such as age at the time of survey, current place of residence (urban/rural), years of schooling, religion, caste, and child's sex and birth weight. A modest J-shaped relationship between birth order of children and their risk of dying in the neonatal period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 61 publications
5
35
0
Order By: Relevance
“…The implication of this form of selection for mortality is a priori ambiguous. Whereas some studies found a J-shaped relationship between infant mortality and birth order (e.g., Hobcraft et al 1985;Pandey et al 1998), with firstborns showing the elevated risks, others found a linearly increasing risk from earlier-born to later-born children, which could protect earlier-born girls (e.g., Mishra et al 2018). Basu and De Jong (2010) hypothesized that in a context with son preference, earlier-born daughters may experience negative consequences for their well-being as a result of having to assist in the care of laterborn children within their families.…”
Section: Explicit and Implicit Discrimination Processes That Contribumentioning
confidence: 99%
“…The implication of this form of selection for mortality is a priori ambiguous. Whereas some studies found a J-shaped relationship between infant mortality and birth order (e.g., Hobcraft et al 1985;Pandey et al 1998), with firstborns showing the elevated risks, others found a linearly increasing risk from earlier-born to later-born children, which could protect earlier-born girls (e.g., Mishra et al 2018). Basu and De Jong (2010) hypothesized that in a context with son preference, earlier-born daughters may experience negative consequences for their well-being as a result of having to assist in the care of laterborn children within their families.…”
Section: Explicit and Implicit Discrimination Processes That Contribumentioning
confidence: 99%
“…Eldest boys appear to be in the strongest position of parental investment, with the least risk of stunting [8]. Studies on sibling composition and infant mortality in India found that having older sisters increases risk of female infant mortality regardless of wealth; no sibling effects on male infant mortality were observed [6], [12], [13]. Last born children were also most vulnerable to infant mortality [6].…”
Section: Introductionmentioning
confidence: 96%
“…Analysis of nationally representative 2005–06 data and 2015–16 data from India found that boys were more likely than girls to die in the neonatal period (0–1 month) [5], [6], as would biologically be expected [7]. However, girls were more likely than boys to die in the postnatal period (1–12 months) in 2005–06, contrary to biologic expectation, though no sex difference in postnatal mortality was seen in 2015–16 [5], [6]. These findings suggest the social norm of son preference, which contributes to excess female infant mortality, may be declining [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24][25][26][27] Women who begin childbearing at an early age often have a greater number of children, 28 and this, in turn, is linked to adverse maternal, infant, and child health outcomes. 29 Short birth intervals (< 24 months) 30,31 and higher birth order 32 are also associated with infant and child mortality.…”
Section: Introductionmentioning
confidence: 99%